Therapeutics: Electronic cigarettes for smoking cessation - Hartmann-Boyce, J; Begh, R; Aveyard, P (BMJ Publishing Group, 2018)
A 42 year old electrician has tried to stop smoking several times, including with the aid of pharmacotherapy and behavioural support. He asks you about using electronic cigarettes (EC). His work partner stopped smoking a year ago and is still using EC now. He has heard that EC are as damaging as the real things and worries that if he ends up addicted to EC he’ll not have gained anything. 60% of current adult smokers in Great Britain have tried EC, and 18% are current EC users. In England, over 40% of people who try to stop smoking do so with the aid of an EC. 52% of current EC users are ex-smokers. Some people who stop smoking with an EC are still using the EC a year later. In this article we look at whether EC help people who smoke cut down and stop smoking, whether there are health risks from EC use, and how these compare with smoking.